Desenvolvimento da Geometria através da história: propostas didáticas para o ensino básico - Souza, Adriano Ortiz (2025)
This paper traces the evolution of geometry, from its utilitarian roots in ancient civilizations like the Babylonians and Egyptians, who applied it to practical needs such as construction and land measurement. It highlights the paradigm shift brought by the Greeks, who introduced the rigor of logical demonstration, consolidated by Euclid, transforming mathematics into a deductive science. Finally, Spherical Geometry is explored as a crucial field for understanding our planet, explaining phenomena like flight paths and cartographic projections. Lessons on these topics in elementary and high school are presented as essential for developing spatial reasoning, intellectual curiosity, and problem-solving skills, preparing students for a deeper and more critical understanding of the world.